A study on effective utilization of health care services provided by primary health centre and sub-centres in rural Tamilnadu, India - Rushender, Rajan; Balaji, Ramraj; Parasuraman, Ganesh (International Journal Of Community Medicine And Public Health, 2017)
Background: The utilization rates in public health services systems ranges from 10-30%. The skewed rural/urban availability of public health services is well known. This study has been done to study the extent of utilization of primary health care services in a primary health centre and its Subcentres and the factors associated for the utilization of services. Methods: This descriptive study was conducted at Orathur PHC, Cuddalore district, Tamil Nadu and its sub-centres, covering a population of 45183 by using structured interview schedule with sample size of 3220 (80 houses in each sub-centre) by simple random sampling technique. Results: 60.2% of selected households are located beyond 5 kms. Out of 560 households, 552 are headed by males and the remaining females. 71.96% of study subjects had formal education. 85.5% of respondents were aware of the PHC. 71.2% of respondents had satisfactory opinion about health services. Only 45.40% and 58.80% of the patient`s households with acute & chronic illness had utilized the services at PHC respectively. 81.65% of the ANC mothers had utilized the PHC, 77.98% for TT immunization, 75.24% for delivery, 75.76% for postnatal care, and 79% for immunizing their children. Conclusion: The utilization of primary level services (PHC and Subcentres) is better for preventive and promotive care but is poor for treatment of acute illness, intranatal care and family welfare services, special investigation services.